Probing conformational changes in T7 RNA polymerase during initiation and termination by using engineered disulfide linkages - Ma, Kaiyu (National Academy of Sciences, 2005)
During the transition from an initiation complex to an elongation complex (EC), the single-subunit bacteriophage T7 RNA polymerase (RNAP) undergoes dramatic conformational changes. To explore the significance of these changes, we constructed mutant RNAPs that are able to form disulfide bonds that limit the mobility of elements that are involved in the transition (or its reversal) and examined the effects of the crosslinks on initiation and termination. A crosslink that is specific to the initiation complex conformation blocks transcription at 5–6 nt, presumably by preventing isomerization to an EC. A crosslink that is specific to the EC conformation has relatively little effect on elongation or on termination at a class I terminator (Tφ), which involves the formation of a stable stem–loop structure in the RNA. Crosslinked ECs also pause and resume transcription normally at a class II pause site (concatamer junction) but are deficient in termination at a class II terminator (PTH, which is found in human preparathyroid hormone gene), both of which involve a specific recognition sequence. The crosslinked amino acids in the EC lie close to the upstream end of the RNA–DNA hybrid and may prevent a movement of the polymerase that would assist in displacing or releasing RNA from a relatively unstable DNA–RNA hybrid in the paused PTH complex.